2003
DOI: 10.1016/s1059-1311(03)00002-5
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoencephalographic analysis of bilaterally synchronous discharges in benign rolandic epilepsy of childhood

Abstract: The purpose of this study was to examine the spatial and temporal relationship between bilateral foci of bilaterally synchronous discharges in benign rolandic epilepsy of childhood (BREC) using a whole-scalp neuromagnetometer. We simultaneously recorded interictal magnetoencephalographic (MEG) and electroencephalographic (EEG) signals in six children with BREC. Interictal spikes were classified into three groups: bilaterally synchronous discharges (BSDs), unilateral discharges on right side (UD-R), and unilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…Later studies using whole head MEG localised IEDs 10–20 mm anterior and lateral to the hand somatosensory cortex (with concurrent median nerve stimulation) (Lin et al ., ). Dipole analysis of bilateral discharges showed two ECD sources in homotopic motor areas (Lin et al ., ).…”
Section: Magnetoencephalography In the Idiopathic Focal Epilepsies Ofmentioning
confidence: 97%
See 1 more Smart Citation
“…Later studies using whole head MEG localised IEDs 10–20 mm anterior and lateral to the hand somatosensory cortex (with concurrent median nerve stimulation) (Lin et al ., ). Dipole analysis of bilateral discharges showed two ECD sources in homotopic motor areas (Lin et al ., ).…”
Section: Magnetoencephalography In the Idiopathic Focal Epilepsies Ofmentioning
confidence: 97%
“…A single ECD accounted for most of the unilateral spikes in a pre‐central location and over 98% of spikes were seen simultaneously on EEG and MEG, suggesting a stable tangential dipole source. For bilateral IED, the temporal difference between bilateral foci was 15–21 ms (Lin et al ., ). The same group correlated the location of IED sources with sensory responses (Lin et al ., ), finding IED sources closer to S2 than S1.…”
Section: Magnetoencephalography In the Idiopathic Focal Epilepsies Ofmentioning
confidence: 97%
“…First, it was applied to MEG and EEG forward data simulated with realistic anatomy and real background MEG/EEG signals. Then, it was applied to an MEG experiment (language lexical judgment test) (Fujimaki et al 1999(Fujimaki et al , 2002 and an EEG experiment (bilateral epilepsy) (Lin et al 2003). From the extensive analyses, it will be shown that the proposed approach can enhance the source localization accuracy considerably, compared to the conventional ones.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetoencephalography (MEG) can identify and localize benign Rolandic epileptiform discharges (7, 8). Various neuroradiological abnormalities have been reported in children with benign epilepsy of childhood with centrotemporal spikes (BECTS) (4, 6).…”
mentioning
confidence: 99%